THE INFLUENCE OF LOCATION AND PROMOTION ON INTEREST IN VISITING UPTOWN BREW COFFEE SHOP GREENLAKE CITY TANGERANG - Mimi Enggriani; Freddy Triono; Pusparani Pusparani; Mira Maharani (JPIM (Jurnal Penelitian Ilmu Manajemen), 2023)
This research aims to determine the influence of location and promotion on interest in visiting the Uptown Brew coffee shop, Greenlake City, Tangerang. This type of research is quantitative descriptive with multiple regression analysis methods. Accidental Sampling sampling technique. The population in the study were all visitors who came to Uptown Brew Coffee Shop, Greenlake City, Tangerang. Meanwhile, the sample consisted of 100 people. Partial research results show that location and promotion have a significant effect on visiting interest. A strategic location that is easy to find is the most important thing in opening a business. Promotions carried out by Uptown Brew Coffee Shop include promotions on social media and conventional word of mouth which can provide potential visitors with information and experiences.